The Effect of Word Search Puzzle Games on the Vocabulary of Sixth-Grade Students - Armala; Kurdi Wijaya, Mohammad (Penerbit STKIP PGRI Bangkalan, 2025)
This study investigates the impact of using word search puzzle games as a learning medium on the vocabulary mastery of sixth-grade students at SDN Lantek Timur 2. The research employed a pre- experimental design with a one-group pre-test and post-test model. The results revealed a significant improvement in students’ vocabulary, as evidenced by an increase in the mean score from 54.00 in the pre- test to 82.00 in the post-test. The paired sample t-test showed a significance value of 0.000, indicating a statistically significant difference. Therefore, the word search puzzle game proves to be an effective and engaging tool for enhancing vocabulary skills among elementary school students.